Poverty measurement in Malaysian zakat institutions: A theoretical survey - Mohamed Saladin Abdul Rasool,; Mohd Fauzi Mohd Harun,; Ariffin Mohd Salleh,; Nor Aini Haji Idris, (Penerbit Universiti Kebangsaan Malaysia, 2011)
Economists agreed that the concept of poverty cannot be defined objectivelyHowever, poverty in Malaysia is commonly conceptualized from the perspective of monetary or income. This is a narrow view since it does not consider other vital aspects of poverty such as vulnerability and social exlusion. It is recognized that more attention must be paid to other factors and processes which are either constaining or enhancing the poors ability to make a living in an economically, ecologically and socially sustainable manner.This paper outlines the poverty measurement used by zakat institutions in Malaysia.Besides discussing the present had al-kifayah method, the paper presents the formulation of a multidimensional islamic poverty index (IPI). The proposed multidimensional IPI in nature comprises of monetary and non-monetary indicators and it expected to capture a more holistic way and is expected to have an impact on zakat organizations as it gives a new perspective in measuring poverty.